A Multimodal Discourse Analysis of Promotional Posters in IDB Bali - Wicaksana, GDA; Suprihatin, Yeni; Aminatun, Dyah; Yuniasih, Eka (Universitas Teknokrat Indonesia, 2025)
This study aims to analyze the communication strategy through poster by applying Fairclough 3-Dimentional Model theory. This study analyzes posters from institution which concerns on education, specially design and business in Bali area. This study arises since the change of society due to Covid-19 effect that makes branding becomes very important nowadays and branding through social media is the most popular trend to attract the interest of the visitor page to get the information. The poster analyzed in this study was a poster published in social media which was Instagram, especial Instagram of Institut Desain dan Bisnis Bali. The poster was specified only the poster which has promotional purpose. This study is a descriptive study which applies 3 layers such as text analysis, processing analysis, and social analysis. The result showed that there are 2 comparison discourse patterns, 8 statement discourse patterns, 0 opposite discourse pattern and 2 command discourse patterns which can be concluded that statement discourse pattern is mostly used in IDB Bali Promotional content in which the statement is mostly explaining about the importance of cyber security and the opportunity to learn cyber security in IDB Bali while having the chance to be part of cyber security company.